Improving sleep quality among ICCU patients – evaluating the effectiveness of ear plug and eye mask interventions - Waladani, Barkah; Utami, Wuri; Ernawati; Suwaryo, Putra Agina Widyaswara (European Journal of Clinical and Experimental Medicine, 2024)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Sleep quality is crucial for patient recovery, particularly in critical care settings such as the Intensive Cardiac Care Unit (ICCU). This study aimed to investigate the effectiveness of using eye masks and earplugs in improving sleep quality among ICCU patients. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A quasi-experimental study was conducted using a one-group without control design. A total of 40 ICCU patients were provided with eye masks and earplugs for a minimum duration of three days. Sleep quality was assessed using the Richard Campbell Sleep Questionnaire (RSCQ) before and after the intervention. Data were analyzed using descriptive and inferential statistics. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The use of eye masks and earplugs significantly improved sleep quality among ICCU patients (p<0.05). There was a notable increase in sleep duration, reduction in sleep onset latency, and improvement in sleep efficiency following the intervention. These findings support the efficacy of non-pharmacological interventions in enhancing sleep quality in critical care settings. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The findings highlight the importance of incorporating simple interventions such as eye masks and earplugs into routine care practices in ICCUs to improve patients’ sleep quality.